Tingkat Depresi Mahasiswa Keperawatan di Tengah Wabah COVID-19 - Agus Santoso; Wandria Robi Ardi; Rikhan Luhur Prasetya; Meidiana Dwidiyanti; Diyan Yuli Wijayanti; Muhammad Mu'in; Sarah Ulliya; Fitria Handayani; Madya Sulisno; Maftukhatun Ni’mah; Nur Aas Aisah (Holistic Nursing and Health Science, 2020)
Introduction: The emergence of the COVID-19 pandemic affected the mental health of students. Students feel stressed and sad, anxious, frustrated, confused and do not know how to overcome their conditions. Depression occurs because of negative thinking about oneself and others, so special management is needed in the midst of a COVID-19 pandemic. The aim of this study was to provide an overview of the depression levels of students in the pandemic.Methods: The method in this study was a quantitative research with cross sectional approach. Descriptive analysis is used to provide a description of the level of depression that occurs in students. Data collection used the Beck Deperession Inventory II (BDI II), sampling used a total sample of 148 respondents (students with an average age of 18-20 years old). The process of collecting data is done by using the google form survey method.Results: Students experienced mild mood disorders (25.7%), severe depression (12.2%), low depression (8.1%), moderate depression (0,7%) and extreme (0.7%).Conclusion: Depression in the pandemic of COVID-19 requires special attention in management to prevent mental disorders.